The Role of Sorting Nexin 17 in Cardiac Development - Wu, Yufei; Zhou, Yaqun; Huang, Jian; Ma, Ke; Yuan, Tianyou; Jiang, Yong; Ye, Maoqing; Li, Jun (Frontiers in Cardiovascular Medicine, 2021)
The sorting nexin 17 (SNX17) holds the potential for modulating membrane receptor protein endocytosis and signaling transduction. Our previous study reports the embryonic lethality of homozygous defect of SNX17. Here we aim to investigate the role of SNX17 in rat fetal development. We identify that SNX17 mRNA is widely expressed in multiple tissues of rats with high expression levels in cardiac outflow tract (OFT), and its expression is gradually elevated during cardiac OFT morphogenesis. Homozygous deletion of the gene SNX17 in rats leads to mid-gestational embryonic lethality with congenital heart defects, including double-outlet right ventricle, atrioventricular septal defect, and ventricular septal defect, whereas normal fetal development appears in heterozygotes. Moreover, the migration distance and the number of cardiac neural crest cells are normal during OFT morphogenesis. While cellular proliferation is not affected in the cardiac OFT endocardial cushion, cellular apoptosis is reduced. The transcriptomic analysis further shows that SNX17 deletion results in aberrant gene expression profiles in the cardiac OFT. Thus, the present study suggests that SNX17 is indispensable for cardiac development.